Sikap, Periklanan dan Attitude toward Advertising - Kartika Imasari (Jurnal Manajemen Maranatha, 2010)
Advertising addresses to create consumers' affection and cognition; besides, affect buying behaviour. Advertising also used to create long-term image's product or to trigger sales. It can be formed if we can understand costumer's behaviour which created the advertising itself. The advertising consumer's approval will be influential to goods or services offered.Keywords: attitude, advertising, attitude toward advertising